DBS in the basolateral amygdala improves symptoms of autism and related self-injurious behavior: a case report and hypothesis on the pathogenesis of the disorder - Sturm, Volker; Fricke, Oliver; Buehrle, Christian P.; Lenartz, Doris; Maarouf, Mohammad; Treuer, Harald; Mai, Jürgen K.; Lehmkuhl, Gerd (Frontiers in Human Neuroscience, 2013)
We treated a thirteen year old boy for life-threatening self-injurious behavior (SIB) and severe Kanner’s autism with Deep Brain Stimulation (DBS) in the amygdaloid complex as well as in the supra-amygdaloid projection system. Two DBS-electrodes were placed in both structures of each hemisphere. The stimulation contacts targeted the paralaminar, the basolateral, the central amygdala as well as the supra-amygdaloid projection system. DBS was applied to each of these structures, but only stimulation of the baso-lateral part proved effective in improving SIB and core symptoms of the autism spectrum in the emotional, social and even cognitive domains over a follow up of now 24 months. These results, which have been gained for the first time in a patient, support hypotheses, according to which the amygdala may be pivotal in the pathogeneses of autism and point to the special relevance of the baso-lateral part.